Installing doors and windows [ - Law, Tom; Law, Tom (A fine homebuilding DVD workshop, 1989)
By watching Tom Law you'll learn how to square up and secure an opening window in minutes, set and seal an insulated glass unit in a custom-built frame, shim and plumb a prehung exterior door so it won't sag, size an interior door blank to fit within a site-built frame, make a simple template to align and rout hinge mortises. Learn how to eliminate drafts and to prevent sticking.